Uji Kinerja Bubbling Fluidized-Bed Gasifier Biomassa Menggunakan Katalis Clay - Rahardjo, Bambang Suwondo; Tanaka, Nao (MESIN, 2007)
Performance Test Of Biomass Bubbling Fluidized Bed Gassifier Using Clay CatalystDesign of catalytic bubbling fluidized-bed gasifier operate on temperature 650-750"C using thecheapness ofclay catalyst withoutforming oftar emission compared to silica sand catalyst (13%) and orFCC(1%). Research ofperformance test ofpilot-planthavebeen doneby counted25 timessince year of2004 by biomass feeding in theform ofsawdust, rice husk, corn stem, peanuts shell. Gas product canmove generator diesel 25kWe with calorie value which still lower (<10MJ/ m3), whereas at usage ofcornstemfeeding counted 26 kgs/h at diesel generator 30 kWe, success economize diesel fuel 25% withattainment ofefficiency 51% on gasification temperature of 733"C Still require to improve stability andduration of material feeding system, mixing system design of feeding materialscatalyst, and alsooptimation ofgasification operation condition.